The Effect of Mass ommunication on Individuals (Study of the theory of One Step Flow, Two Steps Flow Multi Steps Flow) - Ahmad Fadhli (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Communication is an interaction activity between one or more with others, the communication process can take place between one direction, two directions and multi directions, along with the development of technology and information science, mass media which currently continues to develop, so that the term mass communication appears which uses mass media as a means of communication, theories in communication science are numerous, including the theory of One Step Flow, Two Steps Flow and Multi Steps Flow. This research focuses on the effect of mass communication on individuals (study of One Step Flow, Two Steps Flow and Multi Steps Flow theories) with a qualitative analysis research model, with literature data sources both through books, journals and others, as well as direct observation in the midst of social life in the development of the media, from the studies conducted, At least it can be concluded that mass communication in general, both one step flow, two steps flow and multi steps flow, does not have a significant effect on the current era, gradually decreasing in its influence, but mass communication can be influenced by the role of opinion leaders and also the conditions and needs of the community for information